2023
DOI: 10.3390/ijms24010762
|View full text |Cite
|
Sign up to set email alerts
|

The Ethanol Extract of Evodiae Fructus and Its Ingredient, Rutaecarpine, Inhibit Infection of SARS-CoV-2 and Inflammatory Responses

Abstract: COVID-19, derived from SARS-CoV-2, has resulted in millions of deaths and caused unprecedented socioeconomic damage since its outbreak in 2019. Although the vaccines developed against SARS-CoV-2 provide some protection, they have unexpected side effects in some people. Furthermore, new viral mutations reduce the effectiveness of the current vaccines. Thus, there is still an urgent need to develop potent non-vaccine therapeutics against this infectious disease. We recently established a series of detecting plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The active site of the 3CL protease has previously been identified, and compounds binding to this site were reported to lead to protein suppression and a reduction in viral replication [ 19 ]. In addition, we previously demonstrated, using an in vitro assay, that rutaecarpine could bind to the active site of the 3CL protease, expressing inhibitory effectiveness towards the protein [ 18 ]. Here, somewhat intriguingly, it was found that RU-75 formed an extra H-bond with the His164 residue, while RU-184 established H-bonds with the Asn142, His164 and Glu166 residues at the desired pocket.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The active site of the 3CL protease has previously been identified, and compounds binding to this site were reported to lead to protein suppression and a reduction in viral replication [ 19 ]. In addition, we previously demonstrated, using an in vitro assay, that rutaecarpine could bind to the active site of the 3CL protease, expressing inhibitory effectiveness towards the protein [ 18 ]. Here, somewhat intriguingly, it was found that RU-75 formed an extra H-bond with the His164 residue, while RU-184 established H-bonds with the Asn142, His164 and Glu166 residues at the desired pocket.…”
Section: Resultsmentioning
confidence: 99%
“…RNA was then extracted, and the levels of TNF-α, IL-6, and IL-1β mRNA were measured by RT-PCR. The RNA extraction and RT-PCR protocol were previously described [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation